Emotion learning - Petruseva, Silvana (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an algorithm which solves the shortest path problem in an arbitrary deterministic environment with "n" states with an emotional agent in linear time. The algorithm originates from an algorithm which in exponential time solves the same problem, and the agent architecture used for solving the problem is an NN-CAA architecture (neural network crossbar adaptive array). By implementing emotion learning, the linear time algorithm is obtained and the agent architecture is modified.
Keywords: emotional agent; complexity; consequence programming; CAA neural network; planning